Crop commercialization in Rwanda: Current market participation and drivers - Warner, James; Benimana, Gilberthe Uwera; Mugabo, Serge; Ingabire, Chantal (International Food Policy Research Institute, 2024)
In this paper, we explore the current levels and participation of crop commercialization by Rwandan smallholder farmers. Our basic unit of analysis is total crop sales divided by the total value of crop production, either at the household or specific crop level. Overall, our findings suggest that approximately 80 percent of farmers participate in crop market sales and sell an average of 33 percent of their total production. However, there is a wide variety of percentage sales by crop and, in general, higher-valued crops are sold by more commercialized farm households. We also find that value of crop production per hectare rises with greater commercialization, suggesting that developing greater market commercialization, particularly with more valuable crops, may increase household incomes and aid in the economic transformation.